Household-level drivers of dietary diversity in transitioning agricultural systems: Evidence from the Greater Mekong Subregion - Ritzema, Randall S.; Douxchamps, Sabine; Fraval, Simon; Bolliger, Adrian M.; Hok, L.; Phengsavanh, P.; Long, C.T.M.; Hammond, James; Wijk, Mark T. van (Elsevier, 2019)
Over the past four decades, agricultural systems in the Greater Mekong Subregion (GMS) have largely evolved from a subsistence orientation toward commercial production, but the multi-faceted changes behind this evolution vary in substance and degree. Despite connoting economic progress, effects of these changes on household welfare indicators such as dietary diversity have been unclear. By taking a comprehensive view of the farm household, this study discerns the drivers of household dietary diversity in this transitional context by linking the Household Dietary Diversity Score (HDDS), as an indicator of dietary diversity, to key household characteristics, livelihood strategies and indicators of farm performance in three study sites in Cambodia, Laos and Vietnam. The Rural Household Multi-Indicator Survey (RHoMIS) tool, a combined survey and analysis platform, was employed to collect data from over 1300 farm households. HDDS is found to increase among the sites in a way that is roughly associated with their state of agricultural transition, though differing combinations of market orientation, specialisation, and intensification traits that describe such a transition suggest that the pathway to commercialisation, and dietary diversity, is not a linear one. Drivers of dietary diversity vary markedly between the sites. In the Laos site, HDDS is most closely correlated to a set of variables closely linked with agricultural transition, while in the Cambodia site it is associated more with other farm and household characteristics. In the Vietnam site, dietary diversity is correlated to the overall value of crop production. Findings point to the need to contextualise site-specific knowledge of linkages between dietary diversity and ongoing agricultural transition in the GMS, as well as policy and interventions seeking to improve dietary diversity in the face of such transition.